Peranan Teori Konstruktivisme Dalam Layanan Bimbingan Karir di SMA - Mardiah, Suci Amelia; N, Neviyarni; Nirwana, Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the contribution of constructivism theory in career guidance services at the Senior High School (SMA) level. With a Systematic Literature Review (SLR) approach, this article examines the contribution of this theory to students’ understanding of themselves and their future. The results of the review indicate that constructivism theory, including the narrative and Life Design approaches, is able to form collaborative interactions between counselors and students in developing meaningful career identities. This study emphasizes the need for a paradigm shift from a directive model to a meaning-based dialogical approach.